Glioblastoma with tumor‐to‐tumor metastasis from lung adenocarcinoma. Issue 6 (15th September 2019) - Fioravanzo, Adele; Simbolo, Michele; Giampiccolo, Davide; Damante, Riccardo; Pinna, Giampietro; Scarpa, Aldo; Barresi, Valeria
Abstract : Glioblastoma is a tumor with widely variable morphology. It may rarely show pseudoepithelial components or true epithelial differentiation. Metastasis to glioblastomas have been previously reported, but were unsupported by immunohistochemical or molecular analyses. Herein we describe a glioblastoma with carcinomatous foci in a patient with no past clinical history of tumors outside the central nervous system. The carcinomatous foci expressed epithelial, but not glial markers. Therefore, whole‐body imaging was carried out to verify the presence of carcinoma. A lung mass was biopsied and it resulted as primary lung adenocarcinoma. Carcinomatous foci of glioblastoma and lung adenocarcinoma had the same KRAS mutation which was absent in glial areas of the glioblastoma. Thus, glioblastoma with tumor‐to‐tumor metastasis was diagnosed. This case demonstrates that, albeit rare, metastases to glioblastoma may occur, and they should be considered in the differential diagnosis of glioblastoma with carcinomatous foci. Even when the past clinical history is negative, the presence of carcinoma should be investigated to rule out glioblastoma with tumor‐to‐tumor metastasis.